Problems faced by the bean farmer in selected areas of Pabna district in Bangladesh - Alam, Mohammad Zamshed; Islam, Md Shariful; Kabir, Muhammad Humayun (Research in Agriculture Livestock and Fisheries, 2018)
The major purposes of the study were to determine the extent of the problem faced by the farmers in bean cultivation and to explore the relationships between bean farmers’ selected characteristics with their problem faced. The study was conducted in four villages of two unions under Atghoria upazilla of Pabna District. Data were collected from a random sample of 106 bean farmers by using an interview schedule during 15 Dec, 2017 to 15 Jan, 2018. The highest proportion (71.70 percent) of the farmers faced medium overall problem in bean production, while 16.04 percent faced high and 12.26 percent faced low problem. Problem faced in non-availability of pesticides ranked 1st and this was followed by non-availability of fertilizers, lack of capital so on and least one lack of irrigation in bean cultivation ranked 28th. Correlation analysis indicated that education, training exposure, organizational participation, extension media contact and farmers’ knowledge had significant negative relationship with their problem faced. Age had significant positive relationship with their problem faced while family members, farm size, annual family income, bean cultivation area, and credit received by the farmers had no significant relationship with their problem faced. Overwhelming (87.74) majority of bean farmers faced medium to high problems therefore, it may be said that problem faced by the farmers in bean cultivation is a serious issue to be addressed to maximize bean production. Res. Agric., Livest. Fish.5(1): 11-18, April 2018